REGULASI DIRI DAN COPING STRESS PADA SISWA - Sisilia Laya; Mastang Ambo Baba; Siti Aisa (JIVA: Journal of Behaviour and Mental Health, 2022)
ABSTRACTThe COVID-19 pandemic is a time that requires students to adapt to new study habits. Students who usually study offline are required to study online. This habit shift causes students to be able to regulate their learning patterns. Students who study online have more workloads than those who study offline. This model causes students to experience learning stress and overcome this. Students must be able to manage their learning and also be able to cope with the stress experienced during online schooling. This study aims to determine how much self-regulation can predict coping with stress. Self-regulation is a process carried out by individuals in determining their actions, achievements, and targets, evaluate achievements or targets and give rewards for what they have achieved. Coping stress is an effort individuals make to overcome and minimize stressful situations. This study uses quantitative research methods that are associative. The research subject was high school students in class X who were experiencing stress while studying online, totaling 147 students. The data collection technique used a self-regulation scale of 24 items and a questionnaire on a stress-coping scale with 23 items. The data analysis results showed a correlation of 0.638 with F = 255.206 and p = 0.000 (p < 0.05), which means that self-regulation is positively and significantly correlated with stress coping. The regression analysis results also show an R Square score of 0.638, meaning self-regulation can predict coping stress by 63.8%.ABSTRAKMasa pendemik covid-19 merupakan masa yang mengharuskan siswa untuk beradaptasi dengan kebiasaan belajar yang baru. Siswa yang biasanya belajar luring diharuskan untuk belajar daring. Peralihan kebiasaan ini mengakibatkan siswa harus bisa mengatur pola belajarnya. Siswa yang belajar daring memiliki beban kerja lebih dibandingkan belajar luring. Hal ini mengakibatkan siswa mengalami stres belajar dan untuk mengatasi hal tersebut siswa harus bisa mengatur belajarnya dan juga bisa mengatasi stres yang dialami selama sekolah daring. Penelitian ini bertujuan untuk mengetahui seberapa besar regulasi diri dapat memprediksi coping stress. Regulasi diri adalah suatu proses yang dilakukan individu dalam menentukan aksi mereka sendiri, pencapainnya, targetnya, mengevaluasi pencapaian atau target serta memberikan penghargaan atas apa yang mereka capai. Coping stressadalah suatu upaya yang dilakukan oleh individu dalam mengatasi serta meminimalisir situasi yang penuh akan tekanan. Penelitian ini menggunakan metode penelitian kuantitatif yang bersifat asosiatif. Subjek penelitian adalah siswa SMA kelas X yang sedang mengalami stres pada saat belajar daring berjumlah 147 siswa. Teknik pengumpulan data menggunakan skala regulasi diri yang berjumlah 24 aitem dan kuesioner skala coping stress berjumlah 23 aitem. Berdasarkan hasil analisis data menunjukkan adanya korelasi sebesar 0,638 dengan F = 255,206 dan p = 0,000 (p < 0,05)? yang artinya regulasi diri berkorelasi positif dan signifikan dengan coping stres. Hasil analisis regresi juga menunjukkan skor R Square sebesar 0,638, artinya regulasi diri dapat memprediksi coping stress sebesar 63,8%.